Cover Feature: Hydrolysis of Peptide Bonds in Protein Micelles Promoted by a Zirconium(IV)‐Substituted Polyoxometalate as an Artificial Protease (Chem. Eur. J. 49/2020). Issue 49 (7th August 2020) - Quanten, Thomas; Savić, Nada D.; Parac‐Vogt, Tatjana N.
Abstract : The hydrolysis of hydrophobic and unstructured proteins is difficult due to their poor solubility in aqueous solutions. This study demonstrates the ability of Zr IV ‐substituted Keggin polyoxometalate (Et2 NH2 )10 [Zr(α‐PW11 O39 )2 ] to promote selective hydrolysis of β‐casein, an intrinsically unstructured protein consisting of 209 amino acids. The amphipathic nature of β‐casein causes it to assemble into large micelles, in which the hydrophilic part of the protein is solvent exposed and able to interact with Zr‐POM that activates peptide bonds towards hydrolysis. More information can be found in the Full Paper by T. N. Parac‐Vogt et al. on page 11170 .